Anatomical Study of Accessory Head of Flexor Pollicis Longus and Its Clinical Significance - Bipinchandra Khade; Gunwant Chaudhari; Nisha Yadav; Ashutosh Mangalgiri (Wolters Kluwer Medknow Publications, 2020)
Background: Cases of nerve entrapment are commonly seen in medical practice. The flexor pollicis longus muscle of the front of the forearm sometimes may have an accessory head. The accessory head of flexor pollicis longus muscle (AHFPL) may compress the anterior interosseus nerve (AIN) to cause weakness of the deep muscles of the front of the forearm. The aim of the present study is to find the incidence of AHFPL and to identify its structural relationships to the median nerve and AIN. Methods: A total of sixty upper limbs of thirty embalmed cadavers were dissected and studied for the presence of AHFPL. Parameters studied were incidence of AHFPL, whether it is bilateral or unilateral, its origin and insertion, and its relationship with AIN. Results: AHFPL was found in 16 cadavers (53%). In 7 out of the 16 cadavers (43.75%), AHFPL was bilateral and in 9 out of 16 cadavers (56.25%), AHFPL was unilateral. AIN was located below the AHFPL in 14 cadavers and in 2 cadavers, it was passing above the AHFPL. The nerve supply of AHFPL was through AIN in the 16 cadavers. Conclusion: Knowledge of AHFPL and its relations with AIN may help medical professionals in diagnosis and treatment as this anatomical variation can lead to compression neuropathy.